IMPLEMENTASI HAK SUBROGASI PERUSAHAAN ASURANSI TERHADAP KENDARAAN YANG DI ASURANSIKAN - Asuan, Asuan (Solusi, 2018)
Approach in normative juridical research, because that legal research is a process to find the rule of law, the principles of law, as well as to address the legal issues faced. Therefore, this type of research is normative with respect to principles and norms in the implementation of subrogation in insurance agreements. In writing with primary and secondary data obtained from literature materials in the form of Act, Perasuaransian, Government Regulation, Civil Code, Trade Codes and literature, lecture materials and other sources related to insurance and problems in particular. The responsibility of the insurance company on the basis of a subrogation right against the insured's loss arising from a third party's mistake, the insurer shall indemnify the insured under the principle of utmost good faith, pursuant to the motor vehicle insurance agreement provided that the insurer is not informed that the losses suffered by the insured are solely not from a third party error. Forms of protection against insurers on the insured who violate the right of subrogation by demanding compensation for the insurer and the third party that the insurer or the insurer can claim back to the insured at any time as long as it is true that the insured has demanded compensation for the third party and at the same time demanding claims against the insurer and the insured is obliged to return some compensation that has been obtained from the insurance claim of insurance vehicles provided, in accordance with the principle of balance or indemnity principle.